On the Possibilities of "Ageing Successfully" with Extensive Physical Impairments - Taghizadeh Larsson, Annika (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2011)
Based on qualitative interviews with Swedish women and men between the ages 65-72 who have been living with physical impairments for a long period of time, this article considers the opportunities and challenges of adopting a leisurely active and self-fulfilling lifestyle in later life if one uses a wheelchair and/or is relatively dependent upon other people’s support. The participants’ accounts point to the importance of considering how social and environmental contexts may influence the meanings and consequences of chronic illnesses and impairments for people of all ages. General developments in welfare, technical improvements, as well as a long line of reforms that include legislation on the adaptation of homes and the Act concerning Support and Service for Persons with Certain Functional Impairments (Lag om stöd och service till vissa funktionshindrade, LSS) are commented upon as changes that have contributed to the leisurely active lifestyle of the interviewees Because it focuses on today’s "young old disabled people" – women and men who have grown up and are growing old during an era of technological advances and developments in the area of disability policies – the article gives voice to a group of people who have been largely overlooked in gerontology and in the literature on the modern, active, "successfully ageing" senior citizen. In research on disability and in disability policy there are, similarly, few references to disabled seniors.